THE ANATOMY OF HUMOUR IN FRIENDS: ANALYSING SARCASM, IRONY, AND SLAPSTICK COMEDY IN A SITCOM PHENOMENON - Amritendu S K; Balakrishnan K (International Journal of Research -GRANTHAALAYAH, 2025)
This paper examines the comedic techniques employed in the television sitcom Friends with a focus on sarcasm, irony, and slapstick. One of the most popular television shows of all time, Friends has captivated audiences since its 1994 premiere with its sharp dialogue, lovable characters, and relatable situations. This study explores the humour strategies at work in the show’s writing and performance by analysing how the comedic elements contribute to the series’ lasting popularity. Through an examination of key scenes and character interactions, this paper examines the tension between verbal wit and physical comedy, revealing how Friends effectively integrates different comedic styles to appeal to diverse audiences. This research also examines how humour functions as a social tool within the show, strengthening friendships and overcoming conflict. Ultimately, this paper provides a detailed examination of Friends’ comedic anatomy, providing insight into why the sitcom remains influential decades after its conclusion.